When democracy incubates inequality and heteronomy: authoritarianism and nationalism in the European Union - Casanova, J. L.; Almeida, J. F. (Sociologia, Problemas e Práticas, 2021)
In this study we analyse the social base of authoritarian and nationalist (AN) parties in the European Union grounded on a theory that articulates social and cultural dimensions. We aim to characterize and understand this electorate, and explain its increase, considering their social class, education, income, social orientations, human values, and attitudes towards immigrants, and looking upon the trajectory of inequalities. Data is from the European Social Survey and contextual national level information on economic and educational inequalities, and on social mobility. We find that AN parties voters are mostly industrial and agricultural workers, with very low educational resources and low income. They are characterized by the social orientation of heteronomy, a paradigmatic conformist disposition combining conformity with inequality and conformity with hetero-determination of one’s social position, here defined by a low score of the human values of equality and creativity. Heteronomy helps to understand a wide range of AN cultural traits of this population such as their exclusionary attitude towards immigrants. And we verify that the expansion of this electorate follows increasing inequality, mainly in education, as well as downward mobility, and social exclusion.